A magyar és a szlovák kis- és középvállalkozói szektor innovációs teljesítményének összehasonlító elemzése - Mile, Csilla; Végh, Katalin; Csath, Magdolna; Éger, Istvánné; Ivicz, Mihály; Schattamann, Ágnes; Takács, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Based on the European Innovation Scoreboard the study intends to provide a compara-tive assessment of the innovation performance of Hungary and Slovakia. The assessment extends to a wide range of indicators covering structural conditions, knowledge creation, innovation at the firm level, R&D expenditures. As catching-up countries Hungary's and Slovakia's innovation performances are well below the EU27 average, but the rate of im-provement is above that of the EU average, especially in case of Slovakia. The low per-formance is attributable to both lagging innovation capabilities in the business sector and an insufficient contribution of public research organizations to the innovation system. There is a need for more stable governance of the innovation system and a more evidence-based approach to policy making in the area of science, technology and innovation policy.